ACCOUNTING FOR MARKETING DECISIONS: ALIGNING COMMUNICATION STRATEGY WITH FINANCE - Loso Judijanto; Abdul Wahab Syakhrani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Accounting for Marketing Decisions is an integrated approach that combines accounting principles with marketing strategies to optimise business decision-making. The concept involves using financial data and accounting metrics to plan, implement, and evaluate marketing communication strategies. The goal is to ensure that marketing decisions are not only effective in achieving communication objectives, but also in line with the company's financial goals. This approach enables companies to allocate marketing resources more efficiently, measure the return on investment (ROI) of marketing campaigns more accurately, and make data-driven strategic decisions to improve overall business performance. The results show that this integrated approach can improve marketing campaign effectiveness, optimise resource allocation, and increase return on investment (ROI). However, its implementation requires organisational changes, including cross-departmental collaboration, the development of integrated information systems, and a change in corporate culture.